Massive thymic hyperplasia in a 15‐month‐old boy: Case report and literature review. Issue 1 (10th November 2018) - Tadiotto, Elisa; Clemente, Maria; Pecoraro, Luca; Piacentini, Giorgio; Degani, Daniela; Pietrobelli, Angelo
Key Clinical Message: A surgical approach is the choice in young infants with MTH, who are furthest from the time of physiological involution of the thymus, and when the thymus achieves the largest relative size, a surgical approach is the choice. Steroid therapy has been shown to be ineffective (4, 9, 16, 18‐20). No surgical complications have been reported, and the outcome is excellent. Recurrence has been seen in only one case. Abstract : A surgical approach is the choice in young infants with MTH, who are furthest from the time of physiological involution of the thymus, and when the thymus achieves the largest relative size, a surgical approach is the choice. Steroid therapy has been shown to be ineffective (4, 9, 16, 18‐20). No surgical complications have been reported, and the outcome is excellent. Recurrence has been seen in only one case.